The evolution and normative recognition of the right to freedom of expression in the Nicaragua legal system - Calderón Marenco , Olga Margine (Scientific journal of social studies, 2024)
The research addresses the legal protection of the right to freedom of expression in Nicaraguan constitutional history from the 19th century to the present day, making a detailed study of the political constitutions that Nicaragua has had as a Republic. It is important to note that the prevailing instability in all legal, political, and institutional processes are the points of agreement found in this constitutional analysis, in addition to the systematic and uniform constitutional treatment given to this right.